Characterizing large-scale quantum computers via cycle benchmarking - Alexander Erhard; Joel J. Wallman; Lukas Postler; Michael Meth; Roman Stricker; Esteban A. Martinez; Philipp Schindler; Thomas Monz; Joseph Emerson; Rainer Blatt (Nature Communications, 2019)
Checking the quality of operations of quantum computers in a reliable and scalable way is still an open challenge. Here, the authors show how to characterise multi-qubit operations in a way that scales favourably with the system’s size, and demonstrate it on a 10-qubit ion-trap device.